Long day's journey into night - O'Neill, Eugene, 1888-1953.; Wood, Peter, 1927-; Olivier, Laurence, 1907-1989.; Cummings, Constance, 1910-2005.; Quilley, Denis; Pickup, Ronald; Lipman, Maureen; Roden, Peter; Pigden, Al.; Annals, Michael; Incorporated Television Company; BFS Video (Firm) (Richmond Hill, Ontario, Canada : BFS Video, 2003)
Depicts a day in the life of a family deteriorating from alcoholism, drug addiction, and imminent death. Ageing actor James Tyrone has abandoned all hope of being a great performer and has settled for being a hack. His bitter wife, Mary, has slipped into morphine addiction, while hie eldest son, Jamie, is a drunk. Jamie is envious of the writing talent of his younger brother, Edmund. These four haunted lives are about to clash.
Special features: biographies; selected works/filmography; Sir Laurence Olivier trivia; Sir Laurence Olivier ... in his own words; Eugene O'Neill ... in his own words; DVD-ROM special features: plays by Eugene O'Neill: "Beyond the horizon", "The emperor Jones" and "Marco Miller".
Art director, Peter Roden ; editor, Al Pigden ; costume designer, Michael Annals ; production designer, Michael Annals.
Laurence Olivier, Constance Cummings, Dennis Quilley, Ronald Pickup, Maureen Lipman.
MPAA rating: Not rated.
DVD, Region 1 encoding, mono.
Keywords: Family problems -- Drama; Actors -- Drama; Husband and wife -- Drama; Brothers -- Drama; Morphine abuse -- Drama; Authors -- Drama; Feature films; Television adaptations